Identification and characterization of suppressor mutants of spl11-mediated cell death in rice - Shirsekar, Gautam S.; Vega-Sanchez, Miguel E.; Bordeos, Alicia; Baraoidan, Marietta; Swisshelm, Andrew; Fan, Jiangbo; Park, Chan Ho; Leung, Hei; Wang, Guo-Liang (Scientific Societies, 2014)
Lesion mimic mutants have been used to dissect programmed cell death (PCD) and defense-related pathways in plants. The rice lesion-mimic mutant spl11 exhibits race nonspecific resistance to the bacterial pathogen Xanthomonas oryzae pv. oryzae and the fungal pathogen Magnaporthe oryzae. Spl11 encodes an E3 ubiquitin ligase and is a negative regulator of PCD in rice. To study the regulation of Spl11-mediated PCD, we performed a genetic screen and identified three spl11 cell-death suppressor (sds) mutants. These suppressors were characterized for their resistance to X. oryzae pv. oryzae and M. oryzae and for their expression of defense-related genes. The suppression of the cell-death phenotypes was generally correlated with reduced expression of defense-related genes. When rice was challenged with avirulent isolates of M. oryzae, the disease phenotype was unaffected in the sds mutants, indicating that the suppression might be Spl11-mediated pathway specific and may only be involved in basal defense. In addition, we mapped one of the suppressor mutations to a 140-kb interval on the long arm of rice chromosome 1. Identification and characterization of these sds mutants should facilitate our efforts to elucidate the Spl11-mediated PCD pathway.